1977
DOI: 10.3189/s002214300002935x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Theory of Indentation of Ice Plates

Abstract: This study gives the results and interpretation of tests made in a cold room on ice plates held vertically in a press and indented at various speeds with a rectangular indentor. These plates, 81 cm square, were held and frozen solid to a steel frame to represent semi-infinite ice sheets. The tests were carried out at — 10°C with indentation speeds varying from 6 × 10 -5 cm/s to 3 cm/s.It was found that the nominal pressure of indentation varies as a function of loading rates in a manner similar to that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Shi et al [51] observed that while the constitutive model accurately captures the compressive creep behaviour under low to moderate strain rates, it potentially overestimates ice strength during iceberg-ship collisions, which involve considerably higher strain rates compared to creep tests. According to Shi et al [51], this overestimation arises because the model does not accommodate the transition from ductile to brittle behaviour, resulting in a continuous exponential growth in stress with strain rate, even past the transition point, after which, based on empirical evidence, the ice strength should plateau or slightly decrease and then increase, with a noticeably lower rate [9,[52][53][54].…”
Section: Viscoelasticitymentioning
confidence: 99%
“…Shi et al [51] observed that while the constitutive model accurately captures the compressive creep behaviour under low to moderate strain rates, it potentially overestimates ice strength during iceberg-ship collisions, which involve considerably higher strain rates compared to creep tests. According to Shi et al [51], this overestimation arises because the model does not accommodate the transition from ductile to brittle behaviour, resulting in a continuous exponential growth in stress with strain rate, even past the transition point, after which, based on empirical evidence, the ice strength should plateau or slightly decrease and then increase, with a noticeably lower rate [9,[52][53][54].…”
Section: Viscoelasticitymentioning
confidence: 99%
“…A widely accepted classical empirical formula was proposed by Korzhavin [1], who conducted extensive research on the characteristics of river ice loads based on measurements of dynamic and static pressures in Siberia. Similarly, Croasdale, Michel, Frederking, and other researchers employed similar on-site or experimental measurement methods [2][3][4], with variations in the types of ice studied, such as lake ice and freshwater ice. Currently, several classification societies and standard organizations, including Bureau Veritas (BV) [5] and the International Organization for Standardization (ISO) [6] recommend using empirically based methods for assessing ice loads.…”
Section: Introductionmentioning
confidence: 99%